2019
DOI: 10.1097/aci.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-associated secondary antibody deficiency

Abstract: Purpose of review: Clozapine has recently been described as a novel cause of secondary antibody deficiency (SAD), associated with long-term therapy. Here we critically review the evidence linking clozapine-use to an increased infection risk, describe immunological alterations, and discuss potential mechanisms. Findings: Individuals with schizophrenia are at 2-5 times more likely to develop pneumonia than the general population, in particular when receiving clozapine. Delayed-onset distinguishes clozapineassoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 75 publications
0
31
0
Order By: Relevance
“…41 Reductions in pneumococcal-specific IgA and IgM were also observed. 43 A longer duration of clozapine use was associated with a higher risk of hypogammaglobulinaemia (annual decline of 0.15 g/l). 42 The magnitude of the reduction was larger than that caused by rituxumab and methotrexate immunosuppressant therapy in rheumatoid arthritis.…”
Section: Pneumoniamentioning
confidence: 96%
See 1 more Smart Citation
“…41 Reductions in pneumococcal-specific IgA and IgM were also observed. 43 A longer duration of clozapine use was associated with a higher risk of hypogammaglobulinaemia (annual decline of 0.15 g/l). 42 The magnitude of the reduction was larger than that caused by rituxumab and methotrexate immunosuppressant therapy in rheumatoid arthritis.…”
Section: Pneumoniamentioning
confidence: 96%
“…Early recent research from one research group has found a reduction in immunoglobulin levels in patients taking clozapine, with a greater effect in those taking long-term treatment. 4143 These studies found clinically significant panhypogammaglobulinaemia and impaired vaccine responses in patients taking clozapine that were not fully explained by smoking or concurrent medication. 41 Reductions in pneumococcal-specific IgA and IgM were also observed.…”
Section: Pneumoniamentioning
confidence: 99%
“…A secondary antibody deficiency has been observed in patients with long-term clozapine use, putting these patients at risk of immunodeficiency. 79 In a retrospective cohort study, clozapine was a possible risk factor for SARS-CoV-2 infection. 80 Although a small study showed that influenza vaccination had no effect on clozapine serum concentrations, 81 vaccination might affect clozapine concentrations through its action on cytochrome P450 metabolism.…”
Section: What Are the Potential Interactions Between Vaccines And Psychotropic Medications?mentioning
confidence: 99%
“…The propensity of clozapine to cause adverse effects such as weight gain may also increase the risk of infection, and there is emerging evidence of a direct effect of clozapine on immunoglobulins. 5 These factors, including the reduction in immunoglobulins, has led to fears that patients taking clozapine might be particularly vulnerable to coronavirus infection. Data have recently been published that confirm these concerns, dem-onstrating that patients taking clozapine are indeed at increased risk for COVID-19.…”
Section: Introductionmentioning
confidence: 99%